2016
DOI: 10.1080/19942060.2016.1224735
|View full text |Cite
|
Sign up to set email alerts
|

Hull shape optimization for autonomous underwater vehicles using CFD

Abstract: Drag estimation and shape optimization of autonomous underwater vehicle (AUV) hulls are critical to energy utilization and endurance improvement. In the present work, a shape optimization platform composed of several commercial software packages is presented. Computational accuracy, efficiency and robustness were carefully considered and balanced. Comparisons between experiments and computational fluid dynamics (CFD) were conducted to prove that a two-dimensional (2D) unstructured mesh, a standard wall functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 18 publications
0
29
0
1
Order By: Relevance
“…The 3-D volume with the following distances relative to the model as presented in Figure 1a was used in this numerical study. The torpedo-like geometry has been designed similar to the studies of Myring [19], Barros et al [20], Gao et al [21], Sousa et al [22], Alam et al [23] by using Myring Equations. The features of Myring equations were formed of a nose, a middle body cylindrical, and a tail section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3-D volume with the following distances relative to the model as presented in Figure 1a was used in this numerical study. The torpedo-like geometry has been designed similar to the studies of Myring [19], Barros et al [20], Gao et al [21], Sousa et al [22], Alam et al [23] by using Myring Equations. The features of Myring equations were formed of a nose, a middle body cylindrical, and a tail section.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 1b, the particular dimensions nose length, middle body length, tail length, diameter, bare hull length, Myring angular parameter, and potential parameter of torpedo-like geometry in the presented study were respectively identified as a=40mm, b=80mm, c=80mm, D=40mm, L=200mm, θ=~30°, and n=2. The selection of these values of the nose and tail parameters was based in previous studies in the literature Myring [19], Barros et al [20], Gao et al [21] Sousa et al [22], Alam et al [23].…”
Section: Methodsmentioning
confidence: 99%
“…The speed range for most AUVs ranges from 3 to 5 kn; therefore, the first two speeds were used for appendage optimization for subsequent chapters, and the last three speeds were used to verify the accuracy of the calculation method. Works by Wu [10] and Dantas and Barros [11], and our previous investigation [6,12] were referred to conducted the validation procedure. As shown in Fig.…”
Section: Validation Of Cfd Simulationmentioning
confidence: 99%
“…An AUV with smaller drag can execute more assignments and save more energy to finish tasks such as detecting and tracking. Historically, the majority of research has focused on optimizing the main hull to reduce drag [1][2][3][4][5][6]. However, modern AUVs have to carry equipment for communication or detection.…”
Section: Introductionmentioning
confidence: 99%
“…Ayrıca, akış ortamındaki türbülanslı koşullardan doğan saçılmaların oluşturacağı verim kayıpları oldukça önemlidir ve benzetilerek kaynakları gösterilebilmelidir [6]. Türbülanslı yapıların ilk meydana geldiği ve sınır tabakanın oluşmaya başladığı bölge gövde üzerinde olduğu için HAD çalışmaları ile uyumlu şekilde gövde formu oluşturulmalıdır [7]. Diğer yandan hava ortamındaki akışlara örnek olarak Sovani ve Chen [8] [11].…”
Section: Gi̇ri̇ş (Introduction)unclassified